As meias confissões de Aninha: sobre a infância e a pobreza - Alves, Ana Carolina (2022)
This dissertation approaches studies related to memory and writing about poverty and childhood in Vintém de Cobre-meias confissões de Aninha, by Cora Coralina. It is a work that is built on the half-confessions of Aninha, Cora Coralina in childhood. Through these poetized confessions flows a universe of everyday facts, characters, objects, places and norms of conduct that come from another time. The poet collects all this memory of her time and lends universal contours. The study of the movement between memory, forgetting and writing was necessary right at the beginning of the dissertation, revealing a panorama that lives the tension between presence and absence. From the studies of this tension, a non-stable lyrical subject is being unraveled, constituting a labyrinth of personalities, some were highlighted here: Aninha, Cora Coralina, Cora-mãe and Cora-citidan. Through the apprehension of the subjects fictionalized by the poet, it was decided to list, mainly Aninha, and to scrutinize some aspects about child- hood and poverty that permeate the entire work. The critical fortune about childhood in the face of some sub-themes: food, toys and games, forms of religiosity, physical punishment and cloth- ing guided the studies and research of the second part of this dissertation, enabling the recon- struction of the childhood scenario experienced by Cora Coralina. This picture was all bordered by poverty, which also gained prominence at the end of this study. In short, a dialogue is built through the poetic matter and the confronted ideology of poverty and childhood.